Bloodwitch / 3. - Dennard, Susan (Dennard, Susan. Witchlands novel., 2019)
Aeduan joins forces with Iseult, a Threadwitch, and the magical girl, Owl, to stop a bloodthirsty horde of raiders from destroying a monastery that holds more than just faith, but to do so he must confront his own father--and his past.